MODAL SOSIAL DAN MODAL MANUSIA PADA PENDIDIKAN JARAK JAUH DI UNIVERSITAS TERBUKA - Parwitaningsih, Parwitaningsih; Darmayanti, Tri (LPPM Universitas Terbuka, 2010)
This article discusses about distance education in the context of sosiological point of view. The discussion emphasizes on the concepts of social capital and human capital, especially, the role of distance education in contributing social capital and human capital in the society. It is also focuses about the contribution social capital and human capital in the distance education institution in Indonesia, that is the Universitas Terbuka. The discussion shows us that distance education institution has the role in improving the human capital that, then, force in increasing the social capital between the human who are involved in the society social network.